2017
DOI: 10.1002/ajmg.b.32607
|View full text |Cite
|
Sign up to set email alerts
|

Genetic overlap between epilepsy and schizophrenia: Evidence from cross phenotype analysis in Hong Kong Chinese population

Abstract: Epilepsy and schizophrenia are common and typical neurological or mental illness respectively, and sometimes they comorbid in the same patients, however the underlying genetic relationship between the two brain diseases is still not fully understood. To investigate the possible genetic contribution to their comorbidity, we performed polygenic risk score (PRS) analyses and genetic correlation estimation so as to identify the overall genetic overlap between the two diseases. The global schizophrenia PRS is stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Previous studies looking for shared genetic links between epilepsy and common genetic comorbidities, using either LDSC 17 or PRS 48 did not identify any shared polygenic signals between epilepsy and its common psychiatric comorbidities 15 . In the study of Gui and colleagues from Hong Kong, the lack of genetic overlap could reflect limited study power for discovery (n=522 epilepsy cases, n=377 schizophrenia cases).…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies looking for shared genetic links between epilepsy and common genetic comorbidities, using either LDSC 17 or PRS 48 did not identify any shared polygenic signals between epilepsy and its common psychiatric comorbidities 15 . In the study of Gui and colleagues from Hong Kong, the lack of genetic overlap could reflect limited study power for discovery (n=522 epilepsy cases, n=377 schizophrenia cases).…”
Section: Discussionmentioning
confidence: 87%
“…PRS analysis has been applied to identify whether schizophrenia-derived PRS could predict casecontrol status in a Hong-Kong based epilepsy cohort, and whether epilepsy PRS (derived from the first ILAE meta-analysis of mostly European epilepsy cases, ILAE 2014) could predict schizophrenia status in a Hong-Kong schizophrenia cohort. It was found that PRS was not predictive, in either direction (Gui et al, 2018). This could be due to the limited power of the first ILAE meta-analysis to detect epilepsy variants confer risk across ethnicities, or an indication that the common genetic architecture of epilepsy and schizophrenia are relatively exclusive.…”
Section: Examining the Genetic Overlap Between Epilepsy And Psychiatr...mentioning
confidence: 98%
“…Likewise, an association with SCZ (3.96 × 10 -5 and 2.44 × 10 -5 ) and MDD ( p = 0.0144 and 0.0314) were identified. A number of studies demonstrating similar genetic overlap between other combinations of mental, medical, and neurologic disorders have also recently appeared 1123 .…”
Section: Shared Individual Variantsmentioning
confidence: 99%